2020
DOI: 10.1371/journal.pone.0232911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between open reduction with internal fixation to circular external fixation for tibial plateau fractures: A systematic review and meta-analysis

Abstract: Peer-reviewed published studies on tibial plateau fractures treated with either open reduction with internal fixation (ORIF) or circular external fixation were reviewed to compare functional, radiological outcomes, postoperative complications, and reoperation rates between the two methods. A systematic search of various databases including Medline, Cochrane Controlled Register of Trials (CENTRAL), ScienceDirect, and Google Scholar from inception until June 2019 was performed. 17 studies with 1168 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…A study compared internal fixation and Ilizarov external fixation for complex tibial plateau fractures which concluded that the number and severity of complications are increased with open reduction and internal fixation while Ilizarov external fixation leads to short hospital stay and functional mobility is achieved earlier. (11) In the present study 76 (76%) patients treated with Ilizarov technique for managing closed tibial plateau fracture had excellent functional outcome, 15 (15%) good outcome, 05 (5%) fair and 04 (4%) poor outcome. In contrast, another study reported excellent results in only around 15%, good in about 60%, fair in about 20% and poor in only 3%.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…A study compared internal fixation and Ilizarov external fixation for complex tibial plateau fractures which concluded that the number and severity of complications are increased with open reduction and internal fixation while Ilizarov external fixation leads to short hospital stay and functional mobility is achieved earlier. (11) In the present study 76 (76%) patients treated with Ilizarov technique for managing closed tibial plateau fracture had excellent functional outcome, 15 (15%) good outcome, 05 (5%) fair and 04 (4%) poor outcome. In contrast, another study reported excellent results in only around 15%, good in about 60%, fair in about 20% and poor in only 3%.…”
Section: Discussionsupporting
confidence: 45%
“…Ilizarov is advantageous in terms of reduction of closed or mini-open fracture with low risk of wound infection, early mobility, functional loading and weight bearing, continuous improvement in reduction and alignment of the bones resulting in early recovery to proper functioning. (11) For cases which may require knee replacement in future, external fixation via ilizarov is a better option as compared to internal fixation as no extensive incisions are made for ilizarov, no soft tissue cover is needed and no introduction of hardware inside the body is required. A study compared internal fixation and Ilizarov external fixation for complex tibial plateau fractures which concluded that the number and severity of complications are increased with open reduction and internal fixation while Ilizarov external fixation leads to short hospital stay and functional mobility is achieved earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Cast bracing and traction produces bad results. Limited open reduction and percutaneous stabilization also do not provide a sufficient reduction of V / VI type highly fragmented injuries, the elongation of the external fixator does not allow for an early range of motion and hinders the healing of joint fractures [13,14]. Dual plating and Open reductionresult in a precise reduction of fragments of fractures and the rebuilding of the joint surface, while at the same time causing excessive soft tissue separation leading to tarnishing and poor wound healing [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported a rate of malunion with Ilizarov fixator ranging from 2% to 21.5% [17][18][19], probably due to either inadequate reduction in the fracture before fixation or loss of wire tensioning and subsequent loss of reduction [16,20]. Li et al [21] performed a systematic review and meta-analysis of peer-reviewed published studies on tibial plateau fractures treated with either open reduction with internal fixation (ORIF) or circular external fixation to compare functional, radiological outcomes, postoperative complications, and reoperation rates between the two methods. Five of 17 studies reported data on malunions.…”
Section: Discussionmentioning
confidence: 99%